Caracterización del proceso de lavado de sal para la empresa INDUSALCA Ltda., Manaure – La Guajira, con fines de automatización (2011)
The next project focused on the adequacy, update and elevation of the quality of the product marine salt washed. These goals were achieved by means of the design of an automatic system applied to the process. It created ideal conditions for the modernisation of the plant, through the generation of designs, drawings and prototypes to automate the process. Applied descriptive methods to make a detailed mapping of the current status of the plant and to identify are the shortcomings in the process and automate what can be optimized; pretending to raise the level of production at a pinch of companies industrialized, causing a large impact on your environment, taking advantage of a better way the production times and optimization of the efficiency.The treated field work in which the conditions in which it runs the project is of a demanding environment where salinity, the high temperatures and dry of the field are factors that have a direct impact on the effective functioning of the devices, it was necessary to base the study on devices that were in some form resistant to extreme conditions that they would be subject, raising in a significant way the costs of the implementation of the system in general. In addition, the investment generated by the implementation contrasted with the benefits offered by this, since the resources, execution times, and the management with regard to the safety systems and fault detection would be administered in a better manner.